Research and Development in Intelligent Systems XXXII Incorporating Applications and Innovations in Intelligent Systems XXIII - Bramer, Max; Petridis, Miltos (Springer International Publishing : Imprint: Springer, 2015)
The papers in this volume are the refereed papers presented at AI-2015, the Thirty-fifth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2015 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Knowledge Discovery and Data Mining, Machine Learning and Knowledge Acquisition, and AI in Action, followed by application stream sections on Applications of Genetic Algorithms, Applications of Intelligent Agents and Evolutionary Techniques, and AI Applications. The volume also includes the text of short papers presented as posters at the conference. This is the thirty-second volume in the Research and Development in Intelligent Systems series, which also incorporates the twenty-third volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field.  .